The Multigenerational Congregation: Meeting the Leadership Challenge - Rendle, Gilbert R. (Rowman & Littlefield Publishers, 2001)
Congregations need to learn new cultural languages and practices in order to speak to and be heard by new generations of people. But how do congregations enter the wilderness of ministry with these new generations when many of those in the entourage do not appreciate the trip? In contrast to many writers about church growth, Rendle works with three important observations: (1) Most congregations are not "pure markets," discrete groups with uniform values and behaviors, that can be targeted to the exclusion of all other audiences; (2) Some of the differences and discomforts experienced in the congregation are based on the members' tenure, or length of membership, rather than their age; and (3) Leadership in congregations is not a matter of marketplace savvy but of spiritual authenticity in which we continue to shape our faith tradition to be heard and understood by a changing culture.